Kualitas Hidup Family Caregiver Pasien Kanker dan Faktor-Faktor yang Mempengaruhinya - Wenny Savitri; Suwarno (MEDIA ILMU KESEHATAN, 2022)
Background: The increase of cancer diagnosis in Indonesia needs special attention because cancer causes crisis not only in patient’s life but also to family caregivers. Studies depict that a family caregiver’s quality of life (QOL) influences patient’s. Therefore, it is necessary to pay special attention to the caregiver’s QOL to generate a holistic approach for cancer patients.Objective: This study aimed to portray family caregivers of cancer patients’ QOL and its associated factors.Methods: In this analytical crossectional study, 60 family caregivers of cancer patients were recruited. The Caregiver Quality of Life Index-Cancer (CQOLC) was used to assess the QOL of family caregivers and then analyzed using descriptive statistics and linear regression.Results: The mean age of the family caregiver was 40±13.67, and 53% were male. The mean score of CQOLC was 43.95 (±17.83). Age was negatively associated with CQOLC score (β= -3.389, p=.034) which meant positively associated with QOL whereas duration of caregiving (β= 2.167, p=.021), cancer stage (β= 1.299, p=.046), and burden of family caregiver (β= 1.292, p=.000) were positively associated with CQOLC score which meant negatively associated with QOL.Conclusion: The study found that the duration of caregiving, cancer stage, and burden were negatively associated with the QOL of the family caregiver. Nursing intervention such as caregiver assistant is needed to decrease the burden to family caregivers, especially when caring for cancer patients with advanced stages.